PENGARUH KOMBINASI BIOCHAR SEKAM PADI DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN LOBAK PADA MEDIA GAMBUT - Prasetyo, sigit Gigih; astina, astina; surachman, surachman (Jurnal Sains Pertanian Equator, 2019)
This study aims to determine the bestdosage of rice husk biochar and NPK fertilizer for the growth and yield of radishes on peat soil. This research was carried out in the experimental garden of the Faculty of Agriculture, Tanjungpura University, Pontianak. This study used a Completely Randomized Design (CRD), which consisted of 6 treatments and 4 replications, each treatment consisting of 3 samples, so that there were 72 plants. P1 = biochar 0 Kg / Ha + NPK 200 Kg / Ha is equivalent to (biochar 0g / polybag + 4g / polybag), P2 = biochar 0Kg / Ha + NPK 400 Kg / Ha (biochar 0g / polybag + NPK 8g / polybag), P3 = biochar 4ton / Ha + NPK 200Kg / Ha (biochar 80g / polybag + NPK 4g / polybag), P4 biochar 4ton / Ha + NPK 400 Kg / Ha (biochar 80g / polybag + NPK 8g / polybag). P5 = biochar 8ton / Ha + NPK 200Kg / Ha (biochar 160g / polybag + NPK 4g / polybag), P6 = biochar 8ton / Ha + NPK 400 Kg / Ha (biochar 160g / polybag + NPK 8g / polybag). The variables observed were tuber wet weight, leaf wet weight, plant dry weight, leaf area, number of leaves, tuber diameter, and tuber length. The results of this study indicate that the combination of rice husk biochar and NPK fertilizer had no significant effect on leaf wet weight, number of leaves, and tuber diameter. The combination of rice husk biochar and NPK fertilizer increased tuber fresh weight, plant dry weight, leaf area, and tuber length with the best dosage was 8 tons biochar / Ha + 400 kg NPK / ha or equivalent to biochar 160 g / polybag + 8 kg NPK / polybag )Keywords: peat soil, radish, rice husk biochar and NPK fertilizer